PENERTIBAN PEDAGANG KAKI LIMA OLEH SATUAN POLISI PAMONG PRAJA KABUPATEN SANGGAU BERDASARKAN PERATURAN DAERAH KABUPATEN SANGGAU NOMOR 15 TAHUN 2017 TENTANG KETERTIBAN UMUM - NIM. A1011201154, MARIO CHRISTIAN LISERO (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractEMPLOYMENT OF STREET VENDORS BY THE SANGGAU DISTRICT PAMONG PRAJA POLICE UNIT BASED ON THE REGULATORY REGULATION OF SANGGAU DISTRICT NUMBER 15 YEAR 2017 ON PUBLIC LIBERTY. The thesis is entitled Controlling Street Vendors by the Sanggau Regency Pamong Praja Police Unit Based on Regional Regulation Sanggau Regency Number 15 of 2017 concerning Public Order. The formulation of the problem of this research This thesis is